Synaptic activity and Alzheimer's disease: a critical update - Tampellini, Davide (Frontiers in Neuroscience, 2015)
Synapses have been known for many years to be the crucial target of pathology in different forms of dementia, in particular Alzheimer’s disease (AD). Synapses and their appropriate activation or inhibition are fundamental for the proper brain function. Alterations in synaptic/neuronal activity and brain metabolism are considered among the earliest symptoms linked to the progression of AD, and lead to a central question in AD research: what is the role played by synaptic activity in AD pathogenesis? Intriguingly, in the last decade, important studies demonstrated that the state of activation of synapses affects the homeostasis of beta-amyloid (Aβ) and tau, both of which aggregate and accumulate during AD, and are involved in neuronal dysfunction. In this review we aim to summarize the up-to-date data linking synaptic/neuronal activity with Aβ and tau; moreover, we also intend to provide a critical overview on brain activity alterations in AD, and their role in the disease’s pathophysiology.